2015
DOI: 10.1177/0034355215573537
|View full text |Cite
|
Sign up to set email alerts
|

Ethics Consultation in Rehabilitation Counseling

Abstract: Ever changing labor market trends and business practices are reshaping how and where certified rehabilitation counselors (CRCs) work and the companies for whom they work

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…The next content analysis of CRCC Advisory Opinions found in the literature was analyzed through 2013. The research concluded that besides The Counseling Relationship and Resolving Ethical Issues sections of the Code, requests for Advisory Opinions on ethical forensic matters were the most requested guidance sought by rehabilitation counselors (Cartwright & Hartley, 2016). As in the 2008 study, CRCs/CCRCs continued to seek guidance on the issues of bias and competency.…”
Section: Brief History Of Rehabilitation Counseling In Forensic Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The next content analysis of CRCC Advisory Opinions found in the literature was analyzed through 2013. The research concluded that besides The Counseling Relationship and Resolving Ethical Issues sections of the Code, requests for Advisory Opinions on ethical forensic matters were the most requested guidance sought by rehabilitation counselors (Cartwright & Hartley, 2016). As in the 2008 study, CRCs/CCRCs continued to seek guidance on the issues of bias and competency.…”
Section: Brief History Of Rehabilitation Counseling In Forensic Settingsmentioning
confidence: 99%
“…Regarding Advisory Opinions, Shaw and Lane (2008) found that only 2% of requests from 1996 to 2006 revolved around business issues. The updated content analysis of Advisory Opinions by Cartwright and Hartley (2016) concluded similarly that 2.6% of opinions pertained to Section K or a total of 12 requests for opinions. In less than a decade, however, five additional requests have been made (Advisory Opinions 131, 132, 135, 142, and 146) through early 2022, two of which overlapped with forensic services.…”
Section: Brief History Of Rehabilitation Counseling In Forensic Settingsmentioning
confidence: 99%
“…Cartwright and Hartley (2016) conducted a content analysis of 127 advisory opinions from 1996 to 2013. These advisory opinions referenced 470 citations to specific sections of the Code.…”
Section: Preventing Violations and Issues Related To Section Amentioning
confidence: 99%
“…Within Section A, the most commonly cited standard had to do with informed consent and professional disclosure. Cartwright and Hartley (2016) stated that “these results are not surprising especially when one considers that the development of a therapeutic relationship and trust is critical to effective rehabilitation practice” (p. 90). Based on this information, CRCs/CCRCs must develop and provide clients with a thorough informed consent and professional disclosure statement and review this statement with clients to ensure understanding.…”
Section: Preventing Violations and Issues Related To Section Amentioning
confidence: 99%
See 1 more Smart Citation